Formulation of stability strategies for business BSF maggot cultivation under hold and maintain conditions at Bumi Farm - Bayu Dwi Prasetyo; Delta Hadi Purnama; Dewi Taurusyanti; Adi Surya Panji Gumilang (Institute of Computer Science (IOCS), 2026)
Food loss and food waste are critical issues at both the national and regional levels. Various efforts have been made to address the accumulation of food waste, one of which is through Black Soldier Fly maggot cultivation. However, previous studies have tended to focus on general strategies and have not specifically integrated a comprehensive analysis of internal and external environments to align business strategies with the company’s position. Therefore, this research aims to formulate a comprehensive alternative business strategy for BSF maggot farming at Bumi Farm in accordance with the business’s position. This Research is a descriptive study. The data used consists of qualitative and quantitative data obtained through observation, interviews, questionnaire, and literature review. The data obtained were analyze using IFE, EFE, IE Matrix, and SWOT analysis. The results of this research indicate Bumi Farm achieved an IFE score of 2.38 and an EFE score of 2.69, both falling into the moderate category. These values place Bumi Farm in Cell V of the IE Matrix with a hold and maintain position. This position indicates that the business’s internal and external conditions are relatively stable but not yet strong enough for expansion. The recommended strategic alternative based on the SWOT matrix is a strategy of stabilizing and strengthening the business internally. The results of this research indicate that the sustainability of the maggot farming business depends not only on expansion but also on strengthening internal capacity and operational stability in the face of business environment dynamics